Analisis Hukum Terhadap Kebijakan Wajib Militer bagi Siswa Bermasalah di Jawa Barat Antara Pembinaan Karakter dan Represivitas Negara - Nur Sri Maryam DM (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The policy proposal by the West Java Provincial Government to introduce mandatory military training for problematic students has sparked public debate concerning its legality, effectiveness, and the state’s approach to addressing juvenile delinquency. This paper analyzes the policy from a legal perspective, particularly in relation to human rights law and the principles embedded in the national education system. Using a normative juridical method with a conceptual and statutory approach, the study finds that the policy potentially violates children's rights, as well as the principles of non-discrimination and fairness in education. Moreover, the coercive approach through military training is deemed incompatible with the spirit of character development, which should be humanistic and participatory. The paper recommends that interventions for problematic students should focus on value-based education, counseling, and empowerment, rather than militarization. Public policy should ensure the protection of children's rights while upholding the principles of proportionality and appropriateness in disciplinary measures.